2020
DOI: 10.1002/mdc3.13006
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Medication Adherence in Parkinson's Disease: A Systematic Review of Contributing Components in Rating Scales

Abstract: Background Poor medication adherence in chronic illnesses such as Parkinson's disease (PD) is a significant but potentially addressable issue if core components are systematically measured. Objective To assess whether rating scales used in PD adequately cover essential components of medication adherence. Methods We accessed 5 databases targeting articles published before October 2019 and using rating scales to measure medication adherence in PD. The ABC Taxonomy from the European Ascertaining Barriers to Compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…However, we would like to briefly discuss a very important issue related to the management of PD patients in real life, which we propose to properly address in a future analysis, in order to implement the still limited data on PD medication adherence. Indeed, it has been demonstrated that a low pharmacological drug adherence among PD patients is common and that it is a widespread phenomenon at all stages [ 33 , 34 ]. It can be related to patients’ intentional and non-intentional factors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we would like to briefly discuss a very important issue related to the management of PD patients in real life, which we propose to properly address in a future analysis, in order to implement the still limited data on PD medication adherence. Indeed, it has been demonstrated that a low pharmacological drug adherence among PD patients is common and that it is a widespread phenomenon at all stages [ 33 , 34 ]. It can be related to patients’ intentional and non-intentional factors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that a low pharmacological drug adherence among PD patients is common and that it is a widespread phenomenon at all stages [ 33 , 34 ]. It can be related to patients’ intentional and non-intentional factors [ 33 ]. Among the latter, the multimorbidity and the increasing complexity of clinical conditions, together with progression, seem the most influencing factors and are increasingly characterized by motor symptoms and severe motor and non-motor complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the presence of depression may impact how participants answer in selfreported questionnaire [51]. At this point, it is also of note to say that the measurement of nonadherence is complex and that the available instruments do not capture all aspects of this construct [52]. However, while the SAMS used in this study may not encompass all aspects of adherence, the key focus of the analysis was put on medication knowledge as a subfactor related to adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Applying the ABC Taxonomy from the European Ascertaining Barriers to Compliance Consortium 23 and World Health Organization recommendations, 24 a recent review on rating scales assessing adherence in Parkinson’s disease concluded that the SAMS – like the Morisky score – assesses both factors of adherence (intentional and non-intentional), and two out of five dimensions of adherence (namely patient and therapy). 25 Regarding the phases of adherence, the Morisky score and the SAMS assesses the implementation and discontinuation of medication, but the SAMS additionally assesses the initiation of medication.…”
Section: Introductionmentioning
confidence: 99%